Size distribution of Platanus acerifolia allergen 3 (Pla a3) in Shanghai ambient size-resolved particles and its allergenic effects. (1st February 2019) - Zhou, Shumin; Zhao, Hui; Peng, Jiaxian; Hong, Qiang; Xiao, Kai; Shang, Yu; Lu, Senlin; Zhang, Wei; Wu, Minghong; Li, Shuijun; Yu, Shen; Wang, Weqian; et al.
Abstract: Pollen allergy has become a major problem for a considerable and steadily increasing percentage of people worldwide. Allergenic protein, which is contained in subpollens, can be released from pollen and suspended in air to cause allergenic reactions. However, the distribution of the allergenic protein and its relationship with inorganic ions in ambient particles has not been reported. Here, a recombinant Platanus acerifolia allergen3 and tandemsix-histidine epitope (His6 ) fusion protein (rPla a3) was expressed in a prokaryotic system and then purified by affinity chromatography. The allergenicity of both rPla a3 and natural Pla a3 in Platanus pollen protein extract was assessed by enzyme-linked immunosorbent assay using the sera of rPla a3-sensitized rats. Our results demonstrated that IgE from rPla a3-sensitized rats could be used to quantify the allergenicity of Pla a3 in the released Platanus pollen and identify the mass level of Pla 3 in size-resolved particles. The peak of natural Pla a3 expression was found in the middle of April, and the highest mass level of Pla a3 occurred in ambient particles diameters larger than 7 μm. The mass concentration of Pla a3 in the atmosphere was consistent with that of the total protein variety, which also showed a peak in particles with diameters larger than 7 μm during the Platanus pollen season. Remarkably, most Pla a3 existed in particulate matters >7 μm, including intact Platanus pollen, and non-negligible partitions of Pla a3 were detected in particles with diameters less than 7.0 μm. Major ions (Ca 2+, NH4 +, and SO4 2− ) in ambient particles not only aggravated pollen rupture and content release, but also affected the distribution of Pla 3 in the particles. Allergic disease could be specifically identified by using rPla a3, and there was a short lag between hospital admission for allergic disease and the peak of Platanus protein concentration in spring. Graphical abstract: Highlights: High titers of IgG and IgE antibodies induced by Pla a 3 were prepared. Pla a 3 was identified in the ambient particles.